Business risk management of Bao Minh insurance company - Nguyễn, Hồng Hoàng Nam (2020)
It can be said that insurance industry is a hot sector in modern life when people have high living standard and their high requirements in protecting themselves and their assets. Bao Minh Insurance Company is assessed to be one of leading insurance service providers in insurance market in Vietnam. There are many aspects to mention about issues in insurance field. However, this research only studied on business risk management of Bao Minh Insurance Company. The author used secondary information to make clear about business risk management of the company. Although the company has achieved lots of success in insurance business as well as risk management of insurance, it still exists limitations and challenges that require the company to recover. Thus, this research also recommends methods and solutions for both Bao Minh Insurance company and the State and Regulatory Agencies at aim to make risk management in insurance field better.